ANALYSIS OF HEALTH LITERACY AND SELF-CARE IN DIABETES MELLITUS ELDERLY - Ezalina; Duri Mandasari; Desti Puswati; Gita Adelia (Universitas Islam Negeri Alauddin Makassar, 2023)
Diabetes mellitus is a disease that causes premature death worldwide and is a major cause of blindness, heart disease, and kidney failure. It is estimated that 1 person dies every 5 seconds from diabetes. The main cause of death is lack of self-care. This is influenced by the individual's ability to understand and access health and use health services (health literacy). This study aimed to find out the analysis of health literacy with self-care for the diabetic elderly. A cross-sectional design was carried out on the elderly who visited Simpang Tiga Health Center Pekanbaru city. 97 elderly people were chosen as the sample through purposive random sampling. Then, the data were analyzed using frequency distribution and chi square test. The results showed that elderly people with good health literacy were only 21 people (21.6%), while 33 people had problems (34.0%), 43 people (44.3%) were inadequate, and 44 people had good self-care (45.4%). ), 27 people were enough (27.8%) and 26 people were lacking (26.8%). There is also a significant relationship between health literacy and self-care of DM patients (p=0.000). Based on the characteristics of the respondents, this study found that education had a significant relationship with self-care (p=0.000). Then, the health literacy sub-variable, understand information and apply information, has a significant relationship with self-care (p=0.000). It is expected for the elderly to always improve themselves in health literacy and carry out self-care in the prevention of diabetes mellitus in the form of diet compliance, regular exercise, identifying symptoms of hyperglycemia and hypoglycemia, regular treatment, and improving quality of life.